Pendampingan Kewirausahaan Pemuda Karang Taruna RW. II Kelurahan Gedawang Banyumanik Semarang - Sutaat Sutaat; Dyah Purwaningrum (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The mentoring program for small business actors was initiated by the Ministry of Cooperatives and Small Medium Enterprises which aims to increase awareness and capabilities for business actors. On the other hand, the program can reduce the high rates of poverty, unemployment, and disparities between regions in Indonesia. Beginning with human resource improvement program activities as executors of activities. It is expected to be able to solve the problems of business actors from various aspects of capital, market, technology, and business governance. The method used in identifying all the problems faced by them as business actors are by using training methods that suit their needs, including entrepreneurship training, market-winning strategies, and mastery of effective and efficient technology and this training can be carried out continuously to increase the profitability company.